Patterns of genomic aberrations suggest that Burkitt lymphomas with complex karyotype are distinct from other aggressive B‐cell lymphomas with MYC rearrangement. Issue 1 (25th September 2012) - Havelange, Violaine; Ameye, Geneviève; Théate, Ivan; Callet‐Bauchu, Evelyne; Mugneret, Francine; Michaux, Lucienne; Dastugue, Nicole; Penther, Dominique; Barin, Carole; Collonge‐Rame, Marie‐Agnès; Baranger, Laurence; Terré, Christine; et al.
Abstract We previously showed that complex karyotypes (CK) and chromosome 13q abnormalities have an adverse prognostic impact in childhood Burkitt lymphomas/leukemias (BL) and diffuse large B‐cell lymphomas (DLBCL). The aim of our study was to identify recurrent alterations associated with MYC rearrangements in aggressive B‐cell lymphomas with CK. Multicolor fluorescence in situ hybridization (M‐FISH) was performed in 84 patient samples (59 adults and 25 children), including 37 BL (13 lymphomas and 24 acute leukemias), 12 DLBCL, 28 B‐cell lymphomas with intermediate features (DLBCL/BL), 4 B‐cell precursor acute lymphoblastic leukemias (BCP‐ALL), and 3 unclassifiable B‐cell lymphomas. New (cytogenetically undetected) abnormalities were identified in 80% of patients. We also refined one‐third of the chromosomal aberrations detected by karyotyping. M‐FISH proved to be more useful in identifying chromosomal partners involved in unbalanced translocations and in revealing greater complexity of 13q rearrangements. Most of the newly identified or refined recurrent alterations involved 1q, 13q and 3q (gains/losses), 7q and 18q (gains), or 6q (losses), suggesting that these secondary aberrations may play a role in lymphomagenesis. Several patterns of genomic aberrations were identified: 1q gains in BL, trisomies 7 in DLBCL, and 18q‐translocations in adult non‐BL. BCP‐ALL usually displayed an 18q21 rearrangement. BL karyotypes were less complex and aneuploid than those of other MYC‐rearranged lymphomas. BCP‐ALL and DLBCL/BL were associated with a higher rate of early death than BL and DLBCL. These findings support the categorization of DLBCL/BL as a distinct entity and suggest that BL with CK are indeed different from other aggressive MYC‐rearranged lymphomas, which usually show greater genetic complexity. © 2012 Wiley Periodicals, Inc.